VERIFICATION AND VALIDATION OF OPEN WATER TEST OF B4-65 B-SERIES PROPELLER MODEL - Machfudin, Andik; Dinariyana, A.A.B.; Sari, Dian Purnama (Journal of Applied Engineering Science, 2023)
Verification and validation (V&V) are essential processes in computational simulations that aim to evaluate the accuracy and reliability of the results compared to experimental data. The quantification of error and uncertainty estimates is crucial in V&V. In this particular study, the open water test of a four-bladed B-series propeller model at 1/6.98 scale was conducted for three advanced coefficients (J = 0.50, J = 0.60, and J = 0.70) at the Indonesian Hydrodynamic Laboratory (IHL). The simulation was conducted under experimental conditions using FINE/Marine 7.2. Verification was performed to estimate the error and the numerical uncertainty USN according to the ITTC convergence ratio R and order of accuracy . The average uncertainty estimated for the thrust and torque coefficient was found to be between 1.72% to 4.81%, with a 95% confidence level. Reducing errors and uncertainties associated with verification and validation in open-water experiments can increase the reliability of numerical simulations.
Keywords: open water, thrust and torque coefficient, uncertainty, verification, validation